Operating System Hardening Based on Privacy, Security and Performance : Customization of Microsoft Windows - Ilonen, Timo (My University, 2024)
Microsoft Windows is the current market leader in the field of desktop operating systems, a position it has held for decades. This mass adoption is driven by a version-based approach, where each new iteration is promoted as an upgrade to users, and old versions are eventually retired, receiving no further support. Yet can each new version truly be considered superior to its predecessor, or is the operating system instead regressing in key areas? Current versions of Windows, Windows 11 in particular, boast ever greater security features, such as Trusted Platform Module (TPM) 2.0 enforcement for hardwarebased security, yet concerns grow over its respect for users’ privacy thanks to increasing telemetry measures. An operating system that is simultaneously more secure, yet cannot itself be trusted, begins sounding like a contradiction of terms. In this thesis, a comprehensive overview of Windows security from both a current and historical perspective is performed. Its current state of data collection is also covered. With this knowledge in mind, the perspective needed to tackle the research challenge - a practical evaluation of Windows in terms of privacy, security, performance and usability - will have been gained. Standardized testing across several versions of the Windows operating system was conducted, from Windows XP to Windows 11, as well as altered versions of Windows 11 running under a virtual environment. Ubuntu, a Linux distribution, was also included for comparison. The purpose of this testing was to accurately gauge the current state of Windows in these key areas, to predict the direction it is likely to be heading, as well as to give recommendations for different user groups regarding their choice of operating system. It was found that Windows has indeed become more resilient to malware over time, though this development already plateaued with Windows 10. Meanwhile, data collection has grown massively with Windows 10 and Windows 11, while performance has slightly decreased. However, third-party modifications provided meaningful improvements in these areas. The operating system’s level of security saw no measurable change, though a system running fewer services may have a smaller attack surface. Linux was found to excel in system performance in particular.
Keywords: Microsoft Windows, operating system security, malware, telemetry, system performance